Long-term efficacy and tolerability of lemborexant compared with placebo in adults with insomnia disorder: results from the phase 3 randomized clinical trial SUNRISE 2. Issue 9 (26th June 2020) - Kärppä, Mikko; Yardley, Jane; Pinner, Kate; Filippov, Gleb; Zammit, Gary; Moline, Margaret; Perdomo, Carlos; Inoue, Yuichi; Ishikawa, Kohei; Kubota, Naoki
Abstract: Study Objectives: To assess long-term efficacy and safety of lemborexant (LEM), a novel dual orexin receptor antagonist, versus placebo in adults with insomnia disorder. Methods: This was a 12-month, global, multicenter, randomized, double-blind, parallel-group phase 3 study comprising a 6-month placebo-controlled period (reported here) followed by a 6-month active-treatment-only period (reported separately). A total of 949 participants with insomnia (age ≥18 years) were randomized, received treatment with an oral dose of placebo or LEM (5 mg [LEM5] or 10 mg [LEM10]) and were analyzed. Sleep onset and sleep maintenance endpoints were analyzed from daily electronic sleep diary data. Treatment-emergent adverse events (TEAEs) were monitored throughout the study. Results: Decreases from baseline in patient-reported (subjective) sleep onset latency and subjective wake after sleep onset, and increases from baseline in subjective sleep efficiency, were significantly greater with LEM5 and LEM10 versus placebo. Significant benefits over placebo were observed at the end of month 6, and at most time points assessed over the 6-month period, indicating long-term sustained efficacy of LEM. A significantly greater percentage of sleep onset responders and sleep maintenance responders were observed with LEM treatment versus placebo. Participants treated with LEM reported a significant improvement in quality of sleep after 6 months versus placebo. The majority of TEAEs were mild or moderate. There was a low rate of serious TEAEs and no deaths. Conclusions: LEM5 and LEM10 provided significant benefit on sleep onset and sleep maintenance in individuals with insomnia disorder versus placebo, and was well tolerated. Clinical trial registration: ClinicalTrials.gov, NCT02952820; ClinicalTrialsRegister.eu, EudraCT Number 2015-001463-39